Contemporary Lights on Apuleius the Madorite and his Novel "The Golden Donkey"/ "Metamorphoses" - Sabah, Béarcia (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims to introduce the personality of Apuleius (125 AD-around 170 or 180 AD) and his novel "The Golden Donkey," as well as to establish its literary impact on the modern novel. Methods: The research is based on a critical historical methodology, highlighting the influence of political, social, and cultural conditions on literature of that era. This involves referring to primary sources and recent references, comparing and analyzing their scientific material, and reformatting it after re-linking. The study attempts to capture the difference between Latin literature and Latinophone literature (written in Latin). For reference, an Arabic translation of the novel was used rather than the original Latin version. Results: The results illustrate the contribution of this Maghrebi figure to world literature, Apuleius’s place in Latin literature, and his connection to the land and local culture (Amazigh), despite writing in the colonizer’s language (Latin). It emphasizes that attributing works by scholars from the region to the colonizers who settled there since ancient times does not negate their connection to the land, and thus it is necessary to attribute these works to the region rather than the colonizer. It is more accurate to refer to this as Maghrebi Latinophone literature. Conclusions: The research concludes that there is a need to re-evaluate the ancient cultural components of North Africa and correct some common misconceptions in the history of the region’s scientific thought, including attributing the works of North African scholars to the languages in which they were written. This involves distinguishing between Latin literature and Latinophone literature (written and spoken in Latin).